2017
DOI: 10.1177/0284185117698865
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancy in fetal head biometry between ultrasound and MRI in suspected microcephalic fetuses

Abstract: Background: Microcephaly is one of the most common fetal structural abnormalities, and prenatal microcephaly is considered a group I malformation of cortical development diagnosed according to ultrasound (US) skull measurements. Purpose: To evaluate the agreement between fetal head US and magnetic resonance imaging (MRI) biometric measurements of suspected microcephalic fetuses. Material and Methods: This institutional review board-approved retrospective study with waived informed consent included 180 pregnant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Moreover, although some studies have demonstrated a good concordance between both techniques for biometry (4)(5)(6), others have shown discrepancies (7). For example, MRI has been found to be more accurate for the definitive diagnosis of microcephaly (8,9), as preliminary US diagnoses were ruled out in 8 out of 30 cases after subsequent MRI analysis. This is valuable, as a small brain size is considered a risk of poor neurodevelopmental outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, although some studies have demonstrated a good concordance between both techniques for biometry (4)(5)(6), others have shown discrepancies (7). For example, MRI has been found to be more accurate for the definitive diagnosis of microcephaly (8,9), as preliminary US diagnoses were ruled out in 8 out of 30 cases after subsequent MRI analysis. This is valuable, as a small brain size is considered a risk of poor neurodevelopmental outcome.…”
Section: Introductionmentioning
confidence: 99%
“…2 Scatterplot of the relationship between the ratio of the transverse diameter of cerebellum to frontal lobe and gestational weeks DISCUSSION Microcephaly is mainly manifested by delayed development of the frontal lobe. At present, there have been reports on the development rules of parameters related to fetal frontal lobe development [5][6][7][8] , which is helpful for the diagnosis of prenatal microcephaly. Since the frontal lobe is more involved in microcephaly than the cerebellum, the ratio of cerebellum to frontal lobe related measurement parameters should theoretically increase in the presence of microcephaly.…”
Section: Resultsmentioning
confidence: 99%
“…A few studies have been reported on the use of prenatal ultrasound to assess normal fetal frontal lobe development, 4-7 but these studies select transthalamic plane and the measurements of frontal lobe were inconsistent. In this research, the transcerebellar plane is chosen as the standard measurement view based on the following reasons:(i) the transcerebellar plane is one of the routine sections for screening fetal central nervous system malformations; (ii) the transcerebellar plane is found to show clearer sylvian fissure than the transthalamic plane, and the sylvian fissure is also an important index for evaluating brain development, which is another important index for evaluating brain development and microcephaly in the current study group; (iii)the ratio of transcerebellar diameter to frontal lobe diameter which means caval-calvarial diameter is also an important indicator for the assessment of microcephaly which has already been reported in another study, 11 but it requires conversion of measurements in the transthalamic and transcerebellar planes, which increases the examination measurement time.…”
Section: Discussionmentioning
confidence: 99%
“…4 A few studies have been reported on the assessment of fetal frontal lobe related developmental parameters in transthalamic plane, but the measurement methods are inconsistent and no uniform reference value is available. 4-7…”
Section: Introductionmentioning
confidence: 99%